First records of Characidium heirmostigmata and C. serrano (Characiformes: Crenuchidae) from freshwaters of Argentina - Casciotta, Jorge; Almirón, Adriana; Doubnerová, Klára; Piálek, Lubomír; Říčan, Oldřich (My University, 2015)
Characidium heirmostigmata and C. serrano are registered for the first time in freshwaters of Argentina in the province of Misiones. Characidium heirmostigmata was found in the middle río Paraná basin and C. serrano in upper and middle río Uruguay basin
Keywords: Characidium heirmostigmata; C. serrano; Characidium heirmostigmata